Fairness and Contractual Performance in Vertical Linkages Within an Uncertain Environment: A Case of a Tomato Value Chain - Amine M. Benmehaia; Antonella Samoggia; Oualid Benharrat; Salah Eddine Benziouche; Georgia Ayfantopoulou (Foods)
In developing countries with uncertain institutional environments, ensuring fairness in contractual arrangements within food value chains is crucial to overcome modern challenges. This paper empirically investigates the vertical relationship between tomato growers and canneries in Algerian agriculture to assess the determinants of contractual performances and price fairness implications. The study is based on an analysis of a comprehensive dataset of 9127 tomato growers engaged in contract farming over four years (2018–2021). Three regression methods were estimated, namely logit, tobit, and quantile regressions, alongside exploratory analysis. The main findings shed light on the factors influencing contractual performance among contracting producers, primarily farm scale and distance from the contracting processor. Additionally, the findings highlight the key role of contract enforcement mechanisms in influencing the contractual performances of tomato growers. Several recommendations are made to incentivize tomato growers and improve overall contractual performance within such public policy settings. Contract arrangements, including fair price negotiation and the requirement for tomato processing firms to make specific investments, are advocated to foster self-enforcement and significantly enhance the growers’ contractual performance. This is particularly important in many developing countries where the business environment is characterized by an absence of effective public enforcement institutions along with a highly uncertain environment.